Foraging Small White Butterflies, Pieris rapae, Search Flowers Using Color Vision - Arikawa, Kentaro; Nakatani, Yoshihiro; Koshitaka, Hisaharu; Kinoshita, Michiyo (Frontiers in Ecology and Evolution, 2021)
We demonstrate that the small white butterfly, Pieris rapae, uses color vision when searching flowers for foraging. We first trained newly-emerged butterflies in a series of indoor behavioral experiments to take sucrose solution on paper disks, colored either blue, green, yellow, or red. After confirming that the butterflies were trained to visit a certain colored disk, we presented all disks simultaneously. The butterflies selected the disk of trained color, even among an array of disks with different shades of gray. We performed the training using monochromatic lights and measured the action spectrum of the feeding behavior to determine the targets’ Pieris-subjective brightness. We used the subjective brightness information to evaluate the behavioral results and concluded that Pieris rapae butterflies discriminate visual stimuli based on the chromatic content independent of the intensity: they have true color vision. We also found that Pieris butterflies innately prefer blue and yellow disks, which appears to match with their flower preference in the field, at least in part.